A smart phone application to evaluate candle frame characteristics - Chatterjee, Abhay; Jeyaseelan, Thangaraja (PREPARE@u® | IEI Conferences, 2021)
Today, smartphones are used for a variety of applications it is not limited to calling and receiving, and sending text messages, they have a variety of features such as a camera, torch, games, social media, news, and so on. This paper aims to utilize the device for yet another application that is capturing the flame height, wick width, and flame width using a smartphone camera. The experimental setup is quite trivial; the camera should be as close as possible to the flame, the reference length has to be measured to have an idea about the total length captured which aids to calculate the pixel length of the image. Further, the change in height and width with respect to time is also recorded.